- Impact of Managers Skills in reduce Job Stress - An Empirical study in some Iraqi Ministries - Rashid, Maysoun Abdel Karim Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
This research aimed to identify the differences skills that the manager have in order to reduce the job stress on individuals working in many organizations. The questionnaire was used as a main tool in obtained the data which divided to two parts each of part of them involve (15)phrases، the first concerned with the managers skills، the second related to the job stress. The research community was limited to random sample in three Iraqi ministries which namely (planning، transport and finance).To analyze the data of the research used the statistical program (SPSS) such means، percentage، person correlation، tests (T، F، Z)، beta coefficient. The results showed significant statistical significance between managers، skills and job stress
Keywords: managers' skills; work pressure